Europe : A Survey of Gender Budgeting Efforts - Quinn, Sheila (IMF Working Papers; Working Paper, 2016)
This paper surveys European gender budgeting efforts, which have enjoyed sustained support for more than a decade and a half. In a number of countries, gender budgeting led to significant changes in budget legislation and administrative practices. In some countries, it is also possible to tie gender budgeting efforts to expenditure and revenue policy reforms. At a time of continued fiscal austerity in Europe, gender budgeting can help inform fiscal policies to ensure gender-related goals are met. Civil society has played an active role in advocating for effective gender budgeting.